ANALYSIS OF PHYSICAL DEMANDS DURING ATTACKING MOVEMENTS FINISHED IN LAYUP, TWO-POINT AND THREE-POINT SHOTS - Anderson Calderani Junior; Rene Augusto Ribeiro; Milton Shoiti Misuta; Luciano Allegretti Mercadante (Federación Extremeña de Balonmano; University of Extremadura, 2020)
The aim of study was characterizing and verify the difference of physical demands during positioned attacks and fast-breaks finished in layups, two-shots and three-shots actions. Physical (velocity and distance covered) and technical (two-point, three-point shoot and layups) parameters were quantified. The attacks were separated in 5-man offense and fast-breaks. For identification of 5-man offense beginning, was utilized criterions based on the positional information of players on court. The fast-breaks were considered all attacks that were not identified by the 5-man offense criteria. All velocity and distance covered data from offensive player were summed up in each attack, producing team's velocity and distance covered. Distance covered in 5-man offense with failed layups were significantly lower than the successful ones. In the comparison between 5-man offense and fast-breaks finished in two-point shots, both variables of the offensive teams were significantly higher for fast-breaks. Greater means also were observed at the distance covered and velocity for the fast-breaks finished with layups. Players need to perform higher distances in their offensive movements for a better performance in layups actions. The similarity of means founded for distance covered and velocity at 5-man finished shots highlights the importance of defensive pressure on the shot's effectiveness. Keywords: Physical demands; technical actions; 5-man offense; fast-break; Demandas físicas; acciones técnicas; ataque posicional; contraataque